Psychiatric Care Setting from the Perspective of Psychiatric Nursing Managers - Vieira, Letícia Carvalho [UNESP]; Bocchi, Silvia Cristina Mangini [UNESP]; MacPhee, Maura; Spiri, Wilza Carla [UNESP] (Bentham Science Publishers, 2025)
Background: Nursing managers are well-positioned to enhance holistic care for patients in psychiatric settings. Managers need to use evidence-based data available to them when making nurse staffing decisions. Patient classification systems can be an excellent source of patients’ priority care needs. Objective: To understand the meaning of using patient classification systems as a management tool for psychiatric nursing managers. Methods: Qualitative study with a content analysis methodological framework. Ten nursing managers from psychiatric institutions in the state of São Paulo participated. Data were collected between August 2016 and May 2017 using a semi-structured interview with recorded audio. Results: The sample consisted of nine women and one man with an average of 14 years’ experience in mental health and seven years of management experience. The psychiatric care setting emerged as a general theme surrounded by four subthemes: current model of decision making, ideal model of decision making, nursing staff dimensioning/staffing, and professional and mental health legislation. Only half of the managers used a patient classification system as a management tool, and there were difficulties associated with their use of the tool. Conclusion: A conceptual model was developed based on the themes, subthemes, categories, and sub-categories in this study. The model demonstrates major differences between psychiatric settings with biomedical models versus psychosocial models. Managers with knowledge of PCS data can better advocate for patients’ holistic needs and adequate nursing resource allocation. Managers may lack the knowledge and skills required for model transformation, and continuing management/leadership education is recommended.
Keywords: Concept formation; Evidence-based nursing practice; Health services administration; Psychiatric nursing; Qualitative research; Role of nursing professionals